Hubungan Antara Keaktifan Siswa dalam Ekstrakurikuler Pramuka dengan Kemampuan Sikap Sosial Siswa Kelas V di SDN Jember Lor 01 Kabupaten Jember - Ade Eka Oktavia (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the relationship between student activity in scouting extracurricular activities and the social attitude skills of fifth-grade students at SDN Jember Lor 01, Jember Regency. This study uses a quantitative approach with a correlational research design. The research sample consisted of 40 students selected using a quota random sampling technique. Data were collected through questionnaires, observations, interviews, and documentation. Data analysis included normality tests, linearity tests, product moment correlation analysis, and coefficient of determination tests. The results of the analysis showed that the data were normally distributed and had a linear relationship. The correlation test produced a correlation coefficient value of 0.809 with a significance value of 0.000 <0.05, so the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. This indicates that there is a positive and significant relationship between student activity in scouting extracurricular activities and their social attitude skills. This relationship is categorized as high. The coefficient of determination test shows that student activity in extracurricular scouting activities contributes 65.44% to students' social attitudes, while the remaining 34.56% is influenced by other factors, both internal and external. This indicates that the higher the student's active participation in extracurricular scouting activities, the higher their social attitude abilities.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Student activeness; Scouting extracurricular activities; Social attitude abilities